Penerapan Metode Mind Mapping dalam Pembelajaran Menulis Puisi pada Peserta Didik Kelas VIII SMP N 02 Tegowanu - Imam Dzulfikar; Nazla Maharani Umaya; Zainal Arifin (Sasindo : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The purpose of this study is to describe the application of the mind mapping method in learning to write poetry for class VIII students of SMP N 02 Tegowanu in the 2021/2022 academic year. The method in this study uses a descriptive qualitative approach. The population in this study were all eighth grade students of SMP N 02 Tegowanu in the 2021/2022 academic year. The sample in this study was class VIII C which was taken using simple random sampling technique. The data collection technique used is a test in the form of poetry writing skills using the mind mapping method and non-test in the form of observation and interviews. The results of the application of the mind mapping method in learning to write poetry for class VIII students of SMP N 02 Tegowanu in the 2021/2022 academic year obtained the highest score of 95 and the lowest score of 75, with the percentage of students' average score of 85%. ABSTRAKTujuan penelitian ini untuk mendeskripsikan penerapan metode mind mapping dalam pembelajaran menulis puisi pada peserta didik kelas VIII SMP N 02 Tegowanu tahun pelajaran 2021/2022. Metode dalam penelitian ini menggunakan pendekatan kualitatif deskriptif. Populasi dalam penelitian ini adalah seluruh peserta didik kelas VIII SMP N 02 Tegowanu tahun pelajaran 2021/2022. Sampel dalam penelitian ini adalah kelas VIII C yang diambil menggunakan teknik simple random sampling. Teknik pengumpulan data yang digunakan yaitu tes berupa keterampilan menulis puisi menggunakan metode mind mapping dan nontes berupa observasi dan wawancara. Hasil penerapan metode mind mapping dalam pembelajaran menulis puisi pada peserta didik kelas VIII SMP N 02 Tegowanu tahun pelajaran 2021/2022 diperoleh nilai tertinggi 95 dan nilai terendah yang didapatkan 75, dengan presentase nilai rata-rata peserta didik 85 %.